Sozialökologisches Systemverständnis: Grundlage für die Modellierung von geographischer Systemkompetenz - Rempfler, Armin; Uphues, Rainer (Zeitschrift für Geographiedidaktik (ZGD), 2010)
The main goal of the article is to present a consistent system theory which is suitable as a basis for the modelling of geographical system competence. An analysis of the system understanding in physical and human geography brings distinct differences to the forefront. The efforts of the scientific discipline specialisations to overcome these differences with the goal of investigating natural and social systems in an integrated manner also prove to be very productive for geography education. Following this discussion and under special consideration of a systemic understanding such as that held by social ecology (according to the Frankfurt school), the relevant system attributes are described. On this basis the cornerstones of a model of system competence in Geography are defined.
Keywords: System concept, system theory, geography education, system competence modelling, social ecology, attributes of systems